Smart Garden on Chili Plants Based on IoT - Simanungkalit, Erwinsyah; Husna, Mardhiatul; Tarigan, Jenny Sari; Suriadi (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Abstract:Cultivating chili plants requires special attention such as temperature and soil humidity. Internet of Things (IoT) technology is a technology that allows objects around us to be connected to the internet network. The widespread adoption of various internet of things technologies has a very pronounced influence in the domestic sector such as home and smart car applications, and the agricultural sector is no exception.Temperature monitoring system, humidityIoT-based soil pan on chili plants (smart garden) is an IoT-based monitoring system design to control temperature and soil moisture on chili plants which can make it easier for farmers to measure soil and plant conditions and to make it easier for farmers to monitor the quality of their agricultural land. The process of creating a monitoring system design begins with interviews to collect primary data and literature studies to collect secondary data. Then carry out system design, tool assembly and implementation. The system for monitoring and controlling temperature and soil moisture using IoT can be run using Windows operating system software. The hardware used is the DHT11 temperature sensor, Moisture Sensor, Arduino, and Nodemcu ESP8266. This system utilizes a pump and fan for its hardware, using an automatic system implementation from a microcontroller so that it can make the hardware run without user intervention.If the humidity value displayed on the LCD is <70% then the pump will be on and the plants will be watered, and if the humidity is >80% then the pump will be off and stop watering.